Dominasi Kedaulatan Negara dalam Integrasi Pemerintahan Uni Eropa: Penolakan Yunani Terhadap Pengungsi Syria - Hirshi Anadza (Universitas Islam Malang, 2019)
Integration becomes a solution when global government does not have capability to overcome power domination of state. By having integration, it is expected that all of member state can put all their authority in supranational governance, such as European Union (EU) so balance could be happen. By giving such kind of integration, the agreement of policies can be followed by the members of EU based on solidarity and tolerance among the members. However, this integration has not succeeded in reducing domination of country sovereignty that influences the variety of each country necessity, even it happen in not powerful state. This phenomenon is reflected when Greece broke the agreement of EU policy related to refugees protection, called Common European Asylum System (CEAS), by refuse asylum seekers from Syria. There are two things that must be highlighted when Greece refuse asylum seekers from Syria. First, domestic problem that can restrain Greece government in obeying CEAS policies. Second, the value of tolerance and solidarity from other countries has not be adhered in the policies agreed by each members of EU. Therefore, this paper explain further about studies to find the relationship between integration in supranational governance and country sovereignty.